Julie tells her story - McDonald, Megan (American girls collection., 2007)
In 1974 at her new San Francisco school, nine-year-old Julie does not want to tell her class about her parents' divorce, or to tell her sister about messing up her school assignment, but when she breaks her finger playing basketball and her whole family rallies around her, she realizes the importance of telling the truth.